Cooperativismo como estrategia de mediación del conflicto escolar (2018)
Cooperativism refers to a set of pedagogical strategies, in which a classroom is organized into small heterogeneous groups, in which the students are conditioned to interact in a conjunctive manner in an environment of cooperation, fraternity, responsibility, respect and tolerance (Johnson & Johnson, 1994). Through cooperativism students are expected to learn to resolve conflicts in the educational establishment taking into account that each person must assume a role during a conflict situation